Kemampuan Siswa1kelas VII SMP Negeri 4 Banda2Aceh Menyimpulkan Isi Surat Dinas - Munifatul Zahara; Razali Razali; Rostina Taib (JIM Pendididikan Bahasa dan Sastra Indonesia, 2019)
The research entitled9"The Ability of Class VII Students of Banda0Aceh State Junior High School 4 in Concluding the Contents of Service Letters" aims to determine the ability of seventh grade students of SMP Negeri 4 Banda Aceh to conclude the contents of official letters. The method used is descriptive quantitative method. Data collection techniques, namely test techniques. Data processing is done using a statistical formula, which is looking for an average value. The results of data processing show that the ability of class VII students of SMP Negeri 4 Banda Aceh to conclude the contents of official letters are in the less category. The average value of ability of class VII students of SMP Negeri 4 Banda Aceh in concluding the contents of official letters is 53. Based on the specific aspects assessed (1) the contents of the official letter, the average value is 62, (2) the contents of official letter requests, the value the average student is 51, (3) the contents of the official letter requirements, the average value of students is 49, and (4) the contents of the official letter request, the average value of students is 51